PENGARUH INTERAKSI EDUKATIF GURU TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV A SD MUHAMMADIYAH 1 BANGKALAN - Anwar, Rahmat Darul; Firmansyah, Ihwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the influence of teacher educational interactions on interest and learning outcomes in mathematics for students in class IV A at SD Muhammadiyah 1 Bangkalan. Based on the output obtained sig 0.000 < 0.05 so it can be concluded that it shows that there is an influence between research subjects using teacher educational interactions on interest and learning outcomes in mathematics. This is proven by the results of students' test questions regarding multiplication of whole numbers which were obtained based on the output that has been tested. The data description shows that there is an average mean at pre of 21.75 while the post data is 34.75. Meanwhile, for independence, based on the output that has been tested, the data description shows that there is an average mean in the pretest of 51.50, while the posttest data is 92.50. So there is an influence of teacher educational interaction on the interest and learning outcomes in mathematics for Class IV A students at SD Muhammadiyah 1 Bangkalan.